A Study on Students’ Ability in Writing Recount Text at Islamic Boarding School Darun Nahdhah Thawalib Bangkinang - Fikry, Hafizhul; Yusrida, Yusrida (State Islamic University of Sultan Syarif Kasim Riau, 2023)
This research aimed to obtaining the data on students’ ability in writing recount text at Islamic Boarding School Daarun Nahdhah Thawalib Bangkinang. This research is a descriptive study consisting of one variable. The researcher used quantitative research. The subjects of this research were students of class XI at Islamic Boarding School Daarun Nahdhah Thawalib Bangkinang, while the object of this research was the students’ ability in writing recount text. The researcher used cluster sampling to take samples, there were 20 students as a sample of 131 students. In collecting the data, the researcher used a test as an instrument and measure by using composition of writing, then analyze using students’ classification. Based on data analysis, the researcher found that the average score of students in writing recount text was 63.33, the lowest score was 54.16, the highest score was 77.08 and the total score was 1266.60. Based on the students’ average scores, this research means that the students’ ability in writing recount text is categorized into a sufficient level.